Complexity of Interferon-γ Interactions with HSV-1 - Bigley, Nancy J. (Frontiers in Immunology, 2014)
The intricacies involving herpesvirus persistence are complex. Herpes simplex virus type 1 (HSV-1) uses a variety of receptors to enter cells, and is transported to and from the host cell nucleus over the microtubule railroad via retrograde and antiretrograde transport. Factors leading to the decision for a replicative virus lytic cycle or latency in the trigeminal ganglion occur on histone 3 (H3) involve the effects of interferon-gamma (IFN-γ) produced by NK cells and noncytolytic CD8+T cells, suppressors of cytokine signaling 1 and 3 (SOCS1 and SOCS3), and M2 anti-inflammatory microglia/macrophages maintained by inhibitory interleukin 10 (IL-10). Both M2 microglia and CD4+CD25+Foxp3+ Treg cells produce IL-10. Histone deacetylases (HDACs) are epigenetic regulators maintaining chromatin in an inactive state necessary for transcription of IFN- γ-activated genes and their antiviral effect. Following the inhibition of HDACs by stressors such as ultraviolet light, SOCS1 and SOCS3 are acetylated, and chromatin is relaxed and available for virus replication. SOCS1 prevents expression of MHC class 1 molecules on neuronal cells and SOCS3 attenuates cytokine-induced inflammation in the area. A model is presented to unify the effects of IFN-, SOCS1, SOCS3, and HSV-1 on H3 and chromatin structure in virus latency or reactivation. HSV-1 latency in the trigeminal ganglion is viewed as an active ongoing process involving maintenance of microglia in an M2 anti-inflammatory state by IL-10 produced in an autocrine manner by the M2 microglia/macrophages and by virus-specific CD4+Foxp3+ Treg cells interacting with virus-specific noncytolytic CD8+ T cells.